Injectable Tumoricidal Neural Stem Cell-Laden Hydrogel for Treatment of Glioblastoma Multiforme—An In Vivo Safety, Persistence, and Efficacy Study - Jasmine L. King; Alain Valdivia; Shawn D. Hingtgen; S. Rahima Benhabbour (Pharmaceutics)
Background/Objectives: Glioblastoma multiforme (GBM) is the most common high-grade primary brain cancer in adults. Despite efforts to advance treatment, GBM remains treatment resistant and inevitably progresses after first-line therapy. Induced neural stem cell (iNSC) therapy is a promising, personalized cell therapy approach that has been explored to circumvent challenges associated with the current GBM treatment. Methods: Herein, we developed a chitosan-based (CS) injectable, biodegradable, in situ forming thermo-responsive hydrogel as a cell delivery vehicle for the treatment of GBM. Tumoricidal neural stem cells were encapsulated in the injectable CS hydrogel as stem cell therapy for treatment of post-surgical GBM. In this report, we investigated the safety of the injectable CS hydrogel in an immune-competent mouse model. Furthermore, we evaluated the persistence and efficacy of iNSC-laden CS hydrogels in a post-surgical GBM mouse model. Results: The injectable CS hydrogel was well tolerated in mice with no signs of chronic local inflammation. Induced neural stem cells (iNSCs) persisted in the CS hydrogels for over 196 days in comparison to 21 days for iNSCs (cell injection) only. GBM recurrence was significantly slower in mice treated with iNSC-laden CS hydrogels with a 50% increase in overall median survival in comparison to iNSCs (cell injection) only. Conclusions: Collectively, we demonstrated the ability to encapsulate, retain, and deliver iNSCs in an injectable CS hydrogel that is well tolerated with better survival rates than iNSCs alone.